2000
DOI: 10.1002/1097-0290(20000820)69:4<440::aid-bit10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance of small-scale CHO perfusion cultures using an acoustic cell filtration device for cell retention: Characterization of separation efficiency and impact of perfusion on product quality

Abstract: Several small‐scale Chinese hamster ovary (CHO) suspension cultures were grown in perfusion mode using a new acoustic filtration system. The separation performance was evaluated at different cell concentrations and perfusion rates for two different CHO cell lines. It was found that the separation performance depends inversely on the cell concentration and perfusion rate. High media flow rates as well as high cell concentrations resulted in a significant drop in the separation performance, which limited the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 53 publications
(52 reference statements)
3
64
0
Order By: Relevance
“…Numerous works in the literature have shown that short-term exposure of cells to the levels of sound intensity used here do not have detrimental effects on cell viability (Gaida et al, 1996;Ryll et al, 2000;Wang et al, 2003). Improvement in the fractionation can be expected by opti mization of the operating parameters and chamber geom etry.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous works in the literature have shown that short-term exposure of cells to the levels of sound intensity used here do not have detrimental effects on cell viability (Gaida et al, 1996;Ryll et al, 2000;Wang et al, 2003). Improvement in the fractionation can be expected by opti mization of the operating parameters and chamber geom etry.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore although the effects of low culture temperature on the cellular productivity of recombinant proteins are variable and depend on the temperature, cell line, clone, expression system and/or protein, the effect of reducing cell growth is a universal phenomenon Ohsuye 1998, 1999;Kaufmann et al 1999;Ryll et al 2000;Schatz et al 2003;Yoon et al 2003aYoon et al , b, 2004Yoon et al , 2006Fox et al 2004;Fogolin et al 2004, Bollati-Fogolin et al 2005Trummer et al 2006;Al-Fageeh et al 2006). …”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
“…Unlike the case of specific growth rate, effects of lowering culture temperature on specific productivity may not be generalized. In many reports, the specific productivity of hybridoma, BHK, and CHO cells was not enhanced by lowering of the culture temperature [26,33,38,39,42,43]. On the other hand, there are few reports that the specific productivity of CHO cells increased at low temperature [37,44].…”
Section: Effect Of Temperaturementioning
confidence: 99%